The worsening divergence of biotechnology: the importance of risk culture - Trump, Benjamin D.; Cummings, Christopher L.; Loschin, Nicholas; Keisler, Jeffrey M.; Wells, Emily M.; Linkov, Igor (Frontiers in Bioengineering and Biotechnology, 2023)
In the last twenty years, the field of biotechnology has made significant progress and attracted substantial investments, leading to different paths of technological modernization among nations.As a result, there is now an international divide in the commercial and intellectual capabilities of biotechnology, and the implications of this divergence are not well understood. This raises important questions about why global actors are motivated to participate in biotechnology modernization, the challenges they face in achieving their goals, and the possible future direction of global biotechnology development. Using the framework of prospect theory, this paper explores the role of risk culture as a fundamental factor contributing to this divergence. It aims to assess the risks and benefits associated with the early adoption of biotechnology and the regulatory frameworks that shape the development and acceptance of biotechnological innovations. By doing so, it provides valuable insights into the future of biotechnology development and its potential impact on the global landscape.